Chromatosim 1 : a user-friendly equilibrium theory of chromatography simulator. - Woo, Weng Foong. (2010)
Chromatography is a widely used method of physical separation of mixtures into pure components based on the principle of adsorption. Chromatographic problems are solved analytically using the equilibrium theory of chromatography where assumptions such as negligible axial dispersion and local equilibrium are made. The theory results in a simplified mass balance equation, a 1st order PDE which is solved by the method of characteristics. The various isotherms considered are linear and competitive Langmuir isotherms for both single and binary component systems. The latter requires a more sophisticated method of characteristics where the solutions on a physical plane extend to hodograph and omega characteristic planes as well. The wave interactions of same and different families under a Langmuirian behavior are explored which are important to analyze a complete chromatographic cycle. Hence, a user-friendly chromatographic simulator, ChromatoSim 1 based on the equilibrium theory is developed in Matlab and the analytical simulation results are validated with the results from numerical simulations.